Synthesis of (4R)- and (4S)-[4-2H1] Geraniol - Lee, D.H.; Song, H.A.; Shin, E.H.; Lee, E.J.; Kim, Y.Y.; Jung, D.I.; Hahn, J.T. (Asian Journal of Chemistry, 2011)
The pinene synthase (cyclase) from common sage (Salvia officinalis) catalyzes the conversion of geranyl pyrophosphate to the bicyclic olefins (+)-α-pinene and (+)-β-pinene (cyclaseIII), in addition to smaller amounts of monocyclic and acyclic monoterpene olefins. To obtain conclusive evidence concerning the stereospecificity of deprotonation in the biosynthesis of (+)- and (-)-α- pinene, we synthesized geraniol labeled stereospecifically with deuterium at C-4.